2009
DOI: 10.1017/s0140525x09991361
|View full text |Cite
|
Sign up to set email alerts
|

Belief in evolved belief systems: Artifact of a limited evolutionary model?

Abstract: From an evolutionary standpoint, a default presumption is that true beliefs are adaptive and misbeliefs maladaptive. But if humans are biologically engineered to appraise the world accurately and to form true beliefs, how are we to explain the routine exceptions to this rule? How can we account for mistaken beliefs, bizarre delusions, and instances of self-deception? We explore this question in some detail. We begin by articulating a distinction between two general types of misbelief: those resulting from a br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…). In a complementary vein, population-genetic level explanations of psychological functions are being taken to task by evolutionary systems approaches, the latter of which is inherently systems oriented and critical of simple, single cause genetic explanations (Gottlieb 2002;Gottlieb & Lickliter 2007;Griffiths & Stotz 2000;Lickliter & Honeycutt 2003;Lickliter 2008;Oyama 1985Oyama , 2000Wereha & Racine 2009a. However, although contemporary comparative work has found that many capabilities that have historically been understood to be uniquely human are harder to separate from those of some other species, the conceptual nexus of these issues is rarely considered in psychological theory.…”
Section: Introductionmentioning
confidence: 99%
“…). In a complementary vein, population-genetic level explanations of psychological functions are being taken to task by evolutionary systems approaches, the latter of which is inherently systems oriented and critical of simple, single cause genetic explanations (Gottlieb 2002;Gottlieb & Lickliter 2007;Griffiths & Stotz 2000;Lickliter & Honeycutt 2003;Lickliter 2008;Oyama 1985Oyama , 2000Wereha & Racine 2009a. However, although contemporary comparative work has found that many capabilities that have historically been understood to be uniquely human are harder to separate from those of some other species, the conceptual nexus of these issues is rarely considered in psychological theory.…”
Section: Introductionmentioning
confidence: 99%